Exploring the “interactive” hypothesis in adolescents with vision impairment: The relationship between school belonging and selfesteem - Ifigeneia Manitsa; Fiona Barlow-Brown (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2024)
According to the “interactive” hypothesis, global self-esteem is the outcome of the interaction between domain-specific self-esteem and the importance individuals attach to each particular area of the self. This study is the first known attempt to examine the “interactive” hypothesis in adolescents with vision impairment, focusing on the effect of school belonging on self-esteem. Twenty-five adolescents with vision impairment and 19 sighted adolescents, aged 12-18 years, attending mainstream and special schools, participated in this study. Two groups of adolescents with vision impairment participated in this study according to their visual acuity: adolescents with severe sight impairment (previously “blindness” according to the UK classification system) and adolescents with sight impairment (previously “low vision” according to the UK classification system). All the participants completed the revised form of Harter’s Self-Perception Profile (2012) and the Psychological Sense of School Membership (PSSM) scale (Goodenow, 1993a, 1993b). The findings of the study confirmed the hypothesis and showed that the importance attached to specific domains of self-esteem moderates the relationship between school belonging, and domain-specific and global self-esteem in adolescents with and without vision impairment. This study could be considered the first attempt to test the relationship between school belonging and self-esteem in students with severe sight impairment and students with sight impairment, treating them as two different student populations with individual socio-emotional needs. Our findings can be used by professionals who work closely with students with vision impairment (e.g., teachers and rehabilitation officers) to develop educational interventions that will promote their socio-emotional development and self-esteem.